Ecological studies on Cabbage pests - Embaby, E. S. M.; Lotfy, D. E. S. (International Journal of Agricultural Technology, 2015)
A weekly survey of pests present on cabbage crop was undertaken from October 2014 to January 2015. Data show that, several insect pests were found to attack cabbage crops which were identified under three families and two orders. These are the imported Cabbageworm, (Pieris rapae L., Pieridae, Lepidoptera), Cabbage aphid (Brevicoryne brassicae L., Aphididae, Homoptera), Diamondback moth (Plutella xylostella L., plutellidae, Lepidoptera) and Beet armyworm (Spodoptera exigua L.), Noctuidae, Lepidoptera). The most common brassica pests, are Pieris rapae(17.9 %) followed by Cabbage aphid (Brevicoryne brassicae L., (7.59 %) and Plutella xylostella (diamondback moth) was (1.38 %) while Beet army worm (Spodoptera exigua L). which occurred as secondry insect pests on cabbage crop record (0.27 %). Both Diamondback moth (Plutella xylostella L.) and Beet army worm (Spodoptera exigua L) were less collected. Effects of weather factors on population dynamics of the most common cabbage pests were found to decrease if temperature decreased as result of cooler climate as well as increasing the relative humidity R.H. (%) in addition at El-Dair region was higher fungal count spread which caused higher mortality of cabbage pests. Fungi are probably reported as natural enemies more frequently than other pathogen groups such as bacteria. Naturally occurring entomopathogenic fungi have also been shown to occasionally cause high mortality of pest larvae or pupa. During this survey, the incidences of identified entomopathogenic fungi were found to be higher i. e. Metarhizium anisopliae while the bacterium Bacillus thuringiensis was low. Some deaths may have been caused by secondary infections as Aspergillus niger, A. flavus, A. parasiticus, Fusarium sp., Mucor sp. and Rhizopus sp.